Strategi Manajemen Sumber Daya Manusia dalam Menghadapi Tantangan Turnover Karyawan di Hotel-Hotel Berbintang Jakarta - Aditya Pratomo (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Employee turnover in Jakarta’s star-rated hotels remains high in the post-pandemic period, ranging from 11–38% annually, which significantly affects service quality and industry competitiveness. This phenomenon is driven by a combination of job insecurity due to massive layoffs, job stress from excessive workload and long working hours, and a mismatch between young employees’ career expectations and traditional HR practices. Millennials and Gen-Z tend to prioritize self-development, meaningful work, and work–life balance, making them more mobile and open to new opportunities. This study aims to identify the dominant factors influencing turnover, explore the perceptions of HR managers and frontline staff regarding the policy–practice gap, and formulate relevant HR strategies for the post-pandemic context. A qualitative case study approach was employed, involving in-depth semi-structured interviews, non-participant observation, and documentation review, analyzed using Miles, Huberman & Saldaña’s interactive model. Data validity was ensured through triangulation, member checking, and peer debriefing. Findings reveal a significant gap between HR policies and their implementation, weakening retention strategies. The study proposes integrated strategies including consistent employer branding, adaptive and transparent compensation, needs-based digital training, fair work flexibility, and competency-based career mapping. The main contribution lies in formulating a combinatorial HR model that provides a practical retention roadmap while enriching the hospitality HRM literature in Indonesia.